SAP SRM Transformation: Seamless Migration and Performance Optimization - Gopikrishna Yeturi, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The migration and transformation of SAP Supplier Relationship Management (SRM) systems represents a critical challenge in enterprise resource planning implementations. This technical article presents a successful homogeneous migration strategy that maintained the existing operating system environment while enhancing critical components for improved efficiency. The implementation encompassed comprehensive upgrades across multiple domains, including database migration using HANA DB's Backup and Restore functionality, Content Server deployment with advanced security protocols, and MAX DB optimization for enhanced performance. The transformation incorporated sophisticated web infrastructure optimization techniques, leveraging modern load balancing algorithms and implementing advanced caching strategies. Through automated processes and intelligent monitoring systems, the migration achieved significant improvements in system performance, reliability, and operational efficiency. The results demonstrate substantial enhancements in transaction processing capacity, response times, and resource utilization, while simultaneously reducing maintenance overhead and operational costs.
Keywords: Enterprise Resource Planning; SAP Migration; Performance Optimization; System Integration; Infrastructure Modernization